Look Who Is Talking … and Who Is Listening: Finding an Integrative "We" Voice in Entrepreneurial Scholarship. (September 2021) - Dimov, Dimo; Schaefer, Reiner; Pistrui, Joseph
This paper explores the relationship between the study of entrepreneurs and the entrepreneurs we study. While scholars typically adopt a detached, third-person stance for the purpose of explaining and predicting entrepreneurial action, entrepreneurs instead operate in a first-person stance of deciding what to do. The two stances cannot be reduced to one another. We argue that an engaged dialog—a second-person stance—can bring scholars and entrepreneurs together into a unifying practical decision-making perspective. By working to develop this integrative voice in scholarship, we can collapse the dualism of rigor and relevance.